2011
DOI: 10.1245/s10434-011-2076-6
|View full text |Cite
|
Sign up to set email alerts
|

Phyllodes Tumor of the Breast: Role of CD10 in Predicting Metastasis

Abstract: The expression of CD10 can be used to predict the occurrence of distant metastasis in phyllodes tumors of the breast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Al-Masri and colleagues [40] studied the expression of CD10 in 43 cases of PTs and found that positive CD10 expression was significantly associated with the development of distant metastasis (p < 0.05). Ren et al [14] also noted in their study that positive expression of Axl (p = 0.006) and ST6GalNA-cII (p = 0.015) correlated significantly with distant metastasis in PT.…”
Section: Factors Associated With Metastasismentioning
confidence: 99%
“…Al-Masri and colleagues [40] studied the expression of CD10 in 43 cases of PTs and found that positive CD10 expression was significantly associated with the development of distant metastasis (p < 0.05). Ren et al [14] also noted in their study that positive expression of Axl (p = 0.006) and ST6GalNA-cII (p = 0.015) correlated significantly with distant metastasis in PT.…”
Section: Factors Associated With Metastasismentioning
confidence: 99%
“…However, details of stromal overgrowth and atypia are not always included in the histology report. More recent studies have implicated aberrant expression of markers such as CD10, Axl, st6galnacii and epidermal growth factor receptor (EGFR) in malignant progression and the development of distant metastases [27][28][29]. Further studies will be needed to validate these findings, and the main difficulty in obtaining more conclusive results lie in the rarity of malignant phyllodes tumours.…”
Section: Discussionmentioning
confidence: 99%
“…However the expression of certain biological markers could help to determine the pattern of tumor activities and to distinguish the different variants. Consequently, immunohistochemistry for mitotic figures, Desmin and Vimentin determine malignancy while cluster of differentiation 10 (CD10) could predict metastasis [7,8,13]. Tumor genomic studies have shown chromosomal mutation, substitutions and deletions in the cell biology of the malignant variants [2,7].…”
Section: Discussionmentioning
confidence: 99%